Impacts of Agricultural CO2 Emissions, Agricultural Exports and Financial Development on Economic Growth: Insights from East Asia and Pacific Countries - Gafsi, Nesrine; Bakari, Sayef (International Journal of Energy Economics and Policy, 2024)
This study investigates the effects of agricultural CO2 emissions, agricultural exports, and financial development on economic growth in the Asia-Pacific region from 1990 to 2022, using data from 37 countries. The findings reveal that increased capital investment and agricultural exports significantly boost economic growth, while higher final consumption expenditure also plays a crucial role. Conversely, agricultural methane emissions negatively impact economic growth, underscoring the need for sustainable agricultural practices. The analysis highlights the importance of capital accumulation, agricultural sector expansion, and financial development for economic advancement. It also suggests that policies promoting technological innovation, environmental sustainability, and robust domestic demand are essential for sustained economic growth. Future research should address potential biases and explore additional variables to refine these insights.